Quantifying local thickness and composition in thin films of organic photovoltaic blends by Raman scattering - Rodriguez-Martinez,X; Vezie,MS; Shi,X; McCulloch,I; Nelson,J; Goni,AR; Campoy-Quiles,M (Journal of Materials Chemistry C, 2017)
We report a methodology based on Raman spectroscopy that enables the non-invasive and fast quantitative determination of local thickness and composition in thin films (from a few monolayers to hundreds of nm) of one or more components. We apply our methodology to blends of organic conjugated materials relevant in the field of organic photovoltaics. As a first step, we exploit the transfer-matrix formalism to describe the Raman process in thin films including reabsorption and interference effects of the incoming and scattered electric fields. This allows determining the effective solid-state Raman cross-section of each material by studying the dependence of the Raman intensity on film thickness. These effective cross sections are then used to estimate the local thickness and composition in a series of polymer:fullerene blends. We find that the model is accurate within ±10 nm in thickness and ±5 vol% in composition provided that (i) the film thickness is kept below the thickness corresponding to the first maximum of the calculated Raman intensity oscillation; (ii) the materials making up the blend show close enough effective Raman cross-sections; and (iii) the degree of order attained by the conjugated polymer in the blend is similar to that achieved when cast alone. Our methodology opens the possibility of making quantitative maps of composition and thickness over large areas (from microns to centimetres squared) with diffraction-limited resolution and in any multi-component system based thin film technology.